The Role of School Quality and Students’ Health on Academic Achievement: A Binary Probit Regression Study - Bambang Mardi Sentosa; Khusaini Khusaini; Hudaya Latuconsina; Mustofa Kamil; Jarnawi Afgani Dahlan (Jurnal Pendidikan Progresif, 2024)
The Role of School Quality and Students’ Health on Academic Achievement: A Binary Probit Regression Study. Objectives: This study aims to show the effect of school quality, students’ health and s control variables on students’ academic achievement in Tangerang Municipality. Methods: The authors used a representative sample of students who were registered and active in public high schools; 332 samples. The data was obtained by a valid and reliable research instrument through questionnaire. The authors employed Likert scale to measure the variables, while the questionnaire has been distributed to the samples determined by simple random sampling. Findings: The current student’s academic achievement needs to be improved, because the level of achievement was 75% of the predetermined standard. By using a Binary Probit Analysis model, the authors found that the variables of school quality, socioeconomic status, students’ health, and age had significant effect on academic achievement, except the gender. Conclusion: The quality of school and students' health are important instruments for improving student academic achievement. The findings of this study suggested that school principals and their policy makers to always maintain education services by fulfilling school resources, facilities, and teachers’ quality.  Keywords: academic achievement, school quality, socioeconomic status, students’ health.DOI: http://dx.doi.org/10.23960/jpp.v14.i2.202475